2018
DOI: 10.4251/wjgo.v10.i3.71
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatumand colorectal cancer: A review

Abstract: Fusobacterium nucleatum (F. nucleatum) is a Gram-negative obligate anaerobe bacterium in the oral cavity and plays a role in several oral diseases, including periodontitis and gingivitis. Recently, several studies have reported that the level of F. nucleatum is significantly elevated in human colorectal adenomas and carcinomas compared to that in adjacent normal tissue. Several researchers have also demonstrated that F. nucleatum is obviously associated with colorectal cancer and promotes the development of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 101 publications
(160 reference statements)
8
164
0
1
Order By: Relevance
“…Furthermore, although the proportion of cases diagnosed before the age of 50 years increased in all zip code-level income quartiles, the highest proportion of young cases was in the highest income quartile. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. 24 These NCDB data are thought-provoking in that factors typically associated with better access to health care (private insurance, urban geography, and white race) are associated with rising proportions of earlier onset colon cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the proportion of cases diagnosed before the age of 50 years increased in all zip code-level income quartiles, the highest proportion of young cases was in the highest income quartile. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. 24 These NCDB data are thought-provoking in that factors typically associated with better access to health care (private insurance, urban geography, and white race) are associated with rising proportions of earlier onset colon cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have correlated long-term antibiotic use with colorectal adenomas, 25 and multiple associative studies have correlated changes in the gut microbiome with the presence of CRC. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. As expected, an analysis of clinical CRC characteristics stratified by age has shown that CRC detected in younger patients is more advanced with higher rates of regional and distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum is a Gram-negative human oral bacterium 44 that is involved in the pathogenesis of periodontal disease, and is implicated in preterm births 44,45 and cancer. 46,47 F I G U R E 3 A, Illustration of how phase-variable switching of extended hsdS genes occurs. Extended hsdS genes contain three separate target recognition domains (TRDs; TRD 1 in orange at the 5′ end, a central TRD 2a in light green, and TRD 2b at the 3′ end in dark green).…”
Section: Fusobacterium Nucleatum Contain Extended Phase-variable Hsdsmentioning
confidence: 99%
“…Some colonic microbiota, such as Fusobacterium nucleatum and Bacteroides fragilis, are especially potent in activating NF-κB activity [34,35]. Fusobacterium nucleatum is significantly elevated in human colorectal tumors compared to that in adjacent healthy tissue [36], Fusobacterium nucleatum stimulates NF-κB by activating TLR4 signaling and facilitates tumor development [31,37]. Whether colonic microbiota, such as Fusobacterium nucleatum, play roles in the suppression of Siglec ligand expression in colonic epithelial cells will require further investigation.…”
Section: Discussionmentioning
confidence: 99%